An experimental study on the influence of applied voltage on current efficiency of rebars with a modified accelerated corrosion test. (September 2021) - Feng, Weipeng; Dong, Zhijun; Liu, Wei; Cui, Hongzhi; Tang, Waiching; Xing, Feng
Abstract: The present work is focused on the improvement of direct current (DC) accelerated corrosion method for accurate partial corrosion process on full-scale reinforced concrete (RC) and the impact of one of its controlled parameters, the applied voltage, on the current efficiency and electrode reactions. The results showed that an electrolyte circulation process can improve the applicability of the DC localized accelerated corrosion test, with the applied voltage reduced from 30 V to 20 V to overcome the high resistance of concrete. As the electrolyte circulation system drew electrolyte from an external tank, the chloride concentration remained constant during the corrosion process. Further study by an innovative method for electrode-generated gas collection on the influence of applied voltage, chloride concentration and current density on current efficiency showed that most oxygen (one of the secondary reaction products) can be collected and contributed to the quantification of secondary reactions. The applied voltage and chloride concentration are the major factors that determine the quantity of electricity allocation for oxidization of the rebar (primary reaction). The amount of gases decomposed from the rebar tended to be significant when the applied voltage was above 30 V. A low chloride concentration ([Cl − ]/[OH − ] = 0.02) caused more gas generation regardless of the applied voltage. Based on the test results, a modified current efficiency expression was proposed considering the ambiguity of both the valence of iron oxide and the amount of quantity of electricity allocated to multiple reactions.